2007
DOI: 10.1103/physreve.76.061203
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and particle agglomeration in alumina nanofluids: Experiment and theory

Abstract: In recent years many experimentalists have reported an anomalously enhanced thermal conductivity in liquid suspensions of nanoparticles. Despite the importance of this effect for heat transfer applications, no agreement has emerged about the mechanism of this phenomenon, or even about the experimentally observed magnitude of the enhancement. To address these issues, this paper presents a combined experimental and theoretical study of heat conduction and particle agglomeration in nanofluids. On the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
304
8
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 629 publications
(347 citation statements)
references
References 51 publications
31
304
8
4
Order By: Relevance
“…Similar data for nanofluids with particles of Al2O3, SiC and Au were reported in [15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 74%
“…Similar data for nanofluids with particles of Al2O3, SiC and Au were reported in [15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 74%
“…Figs. 14 and 15 indicated the experimental measurements of the thermal conductivity that compared with the thermal conductivity models of many researchers such as Wasp model [19], Hamilton and Crosser [20], Maxwell model [21] and Timo Feeva et al model [22]. These results showed a good agreement between the Wasp model.…”
Section: Measurement Of the Nanofluid Thermal Propertiessupporting
confidence: 72%
“…Other researchers reported that the thermal conductivity enhancement was decreased as concentration increased from 6% to 10% [2]. The same phenomena was observed also when the thermal conductivity was increased as concentration increased from 2% to 10% [3], Al2O3 nanoparticles even though the particle size was almost the same in both the cases. The great disadvantage of larger nanoparticles is that suspensions tend to become unstable.…”
Section: Introductionsupporting
confidence: 63%